Retroclival arachnoid cyst. - Bourekas, E C; Raji, M R; Dastur, K J; Francken, G J; Engle, D J; Nayak, N T (American Journal of Neuroradiology, 1992)
Retroclival arachnoid cyst is a rare mass lesion, with only seven cases previously reported in literature. MR is the imaging modality of choice in its evaluation and in its differentiation from epidermoid cyst. The case reported here was surgically proved and had an uncharacteristic MR signal intensity that was higher than that of cerebrospinal fluid due to previous hemorrhage.